FRAUD AND ANTI-FRAUD IN THE PORT SECTOR - Safuan Safuan (Asia Pacific Fraud Journal, 2018)
The purpose of this study was to determine the anti-fraud and fraud in the port sector. Research method used in this research is qualitative approach, with case study. The results of this study found that fraud was committed by employees (employee fraud), management (management fraud), supplier (vendor fraud), and customer (customer fraud). And for anti-fraud program, the Indonesia Port Corporation has launched IPC clean program as a form of the implementation of Whistle-blowing System.